Overcoming the impact of the COVID‐19 pandemic on oncology early phase trials and drug development in Asia—Experiences and perspectives of the Asian Oncology Early Phase 1 Consortium. Issue 4 (27th January 2021) - Shimizu, Toshio; Kim, Dong‐Wan; Loong, Herbert H.; Lin, Chia‐Chi; Ng, Matthew CH; Yamamoto, Noboru; Ma, Brigette; Tan, Daniel SW
Abstract: Aim: The significance and prioritization of early phase oncology trial continuation during a global pandemic is unknown. This study reported the outcomes, multiple challenges, and broad recommendations associated with the impact of the novel coronavirus disease 2019 (COVID‐19) on oncology early phase 1 trials—and on drug development in Asia—based on the experiences and perspectives of Asian oncology phase 1 centers. Methods: Between March and April 2020 during the initial period of outbreak, the impact of COVID‐19 across oncology phase 1 sites in five Asian countries—China (Hong Kong), Japan, South Korea, Taiwan, and Singapore—was retrospectively analyzed. Results: There was no trial termination or treatment discontinuation in all five countries. Although the most common impact was new patient enrollment being placed on hold, which was based on pharmaceutical sponsors' decision‐making, the situation varied per site. Most sites had no restrictions in place that would limit their ability to fully comply with the requirements of conducting the early phase studies. The number of protocol deviations during the pandemic was largely dependent on domestic transportation status during the outbreak rather than the ability of the clinical trial centers. Conclusion: Determining the risk to benefits ratio of patients with cancer who are enrolled in early phase 1 clinical trials under the unusual circumstances of a global pandemic is important. Specific guidance or guidelines on the conduct of early phase 1 clinical trials during public health emergencies that are based on the recent lessons learned is urgently required. Abstract : First detailed report of the impact of COVID‐19 across oncology phase 1 sites in five Asian countries—China (Hong Kong), Japan, South Korea, Taiwan, and Singapore between March and April 2020 during the midst of pandemic. ‐ There was no trial termination or treatment discontinuation in all five countries. ‐ Most sites had no restrictions in place that would limit their ability to fully comply with the requirements of conducting the early phase 1 studies.